Proceedings of the 5th China High Resolution Earth Observation Conference (CHREOC 2018) - Wang, Liheng; Wu, Yirong; Gong, Jianya; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book is the proceedings of the 5th China High-resolution Earth Observation Conference (CHREOC). The series conference of China High Resolution Earth Observation has been becoming the influential academic event in the earth detection area, and attracting more and more top experts and industry users of related fields. The CHREOCs focus on the popular topics including military-civilian integration, the One Belt and One Road project, the transformation of scientific research achievements, and it also discusses the new ideas, new technologies, new methods, and new developments. The CHREOCs have effectively promoted high-level institutional mechanisms, technological innovation, and industrial upgrading in the high-resolution earth observation area, and arouse the influence of the national-sponsored major project. All papers in this proceeding are from the 5th CHREOC, and most authors are the researchers and experts participating the state major project CHEOS. The papers arethe extraction of research results and reflect the technique level and research direction of the field high-resolution earth observation. All articles have gone through the scientific and strict reviews for several rounds by the experts from the related fields, and therefore reflect the research level and technology innovation of the high-resolution field earth observation. This proceedings will be an informative and valuable reference for both academic research and engineering practice. .
Satellite Energy Prediction and Autonomous Management Technology -- Research on Key Technologies of Geosynchronous SAR Imaging System -- Sea-land Segmentation Algorithm for SAR Images Based on Superpixel-merging -- Vector Quantization: Timeline-based Location Data Extraction and Route Fitting for Crowdsourcing -- Target Aspect Estimation in SAR Images via Two-Dimensional Entropic Thresholding and Radon Transform -- Signal Model and System Parameter Study for Geosynchronous Circular SAR -- Low- light Remote Sensing Images Enhancement Algorithm based on Fully-convolutional Neural Network -- Imaging Algorithm of Arc Array MIMO-SAR Based on Keystone Transform -- PERFORMANCE ANALYSIS OF VEHICLE-BORNE DUAL-BAND DUAL-POLARIZATION WEATHER RADAR -- A New 2D Doppler Steering Method Used for Format Flying Satellites InSAR System -- Research on Imaging Algorithms for Bistatic System of Geosynchronous SAR based on stationary motion mode -- Ultra-short-term Forecasting of Mid-low Altitude Wind Based on LSTM -- Research on Formal Modeling and Analysis of Complex Space Information Systems -- Design of routing incentive protocol for space network based on blockchain technology -- Real-time GF-4 Satellite Image Enhancement in Low Light Conditions -- Development and Prospect of spaceborne infrared Fourier spectrometer -- The ecological function zoning on the hydro-fluctuation belt in Yinzidu reservoir -- High-Speed Object Tracking with Dynamic Vision Sensor -- Analysis of the Algebraic Tails of GF-3 SAR Images. .
Keywords: Signal processing; Geographic information systems; Physical geography; Signal, Speech and Image Processing; Geographical Information System; Earth System Sciences